MELIHAT RASIO RENTABILITAS DARI SUDUT PANDANG GPM, NPM, ROE DALAM MENGUKUR KINERJA LAPORAN KEUANGAN PADA AJB BUMIPUTERA 1912 UNIT SYARIAH JAKARTA - Achmad Fauzi (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2018)
AJB Sharia Bumiputera 1912 is a company engaged in services, namely join life insurance. Its production does not create goods but sell fund products and other services to customers.Methods of data collection is in the final observation, and literature with his analytical methods suchas qualitative analysis. One way to calculate the profits generated by the AJB Sharia Bumiputera1912 can be calculated by using the ratio. One ratio used is the ratio of profitability. In profitabilityratios are ratios such as: GPM (Gross Profit Margin), NPM (Net Profit Margin), ROE (Return OnEquity). To search for results ratio GPM (Gross Profit Margin) takes the total net profit income andoperating expense and the results of 2015 GPM already reached the standard ratio is 17,84%. As forcalculating NPM (Net Profit Margin) takes net income and operating income and the results of NPMin 2015 are 22,42% . And for calculating ROE (Return on Equity) required net income and equitycapital ans the results of ROE in 2015 are 20,15%.